Characterization of supraspinal vasomotor pathways and autonomic dysreflexia after spinal cord injury in F344 rats - Hou, Shaoping; Lu, Paul; Blesch, Armin (Autonomic neuroscience, 2013)
Cardiovascular dysfunction usually occurs after high thoracic and cervical spinal cord injury (SCI). The disruption of supraspinal vasomotor pathways (SVPs) results in the loss of bulbospinal regulation of sympathetic preganglionic neurons, leading to hypotension and compensatory tachycardia at rest. Episodic autonomic dysreflexia can develop upon sensory stimulation below the level of injury. In rodents, the precise spatial distribution of SVPs in the spinal cord originating from the rostral ventrolateral medulla (RVLM) has not been fully defined. To facilitate future studies of axon regeneration to regain cardiovascular control, we injected biotinylated dextran amine (BDA) bilaterally into the RVLM to anterogradely trace SVPs in Fischer 344 (F344) rats. Three weeks later, BDA-labeled descending projections were predominantly localized within the dorsolateral funiculus throughout the cervical and thoracic spinal segments as expected. Additionally, BDA-labeled fibers were also observed in ventral white matter. After a T4 dorsal hemisection to interrupt the dorsolateral funiculus, BDA labeled terminals originating from the ventral white matter as well as serotonergic projections were still detected in regions of autonomic nuclei below the injury. Based on these results, we examined cardiovascular responses after different lesions at spinal level T4, including lateral or dorsal hemisection, dorsolateral or complete transection. Hemodynamic dysfunction and autonomic dysreflexia were only elicited in rats with complete T4 transections when all SVPs were disrupted. Hence, F344 rats with complete T4 transections provide a reliable model for investigating means to improve cardiovascular functional recovery after SCI.
Gesehen am 29.10.2021